Building blocks for one-dimensional van der Waals heterostructures - Xiang Rong; Maruyama Shigeo; Li Yan (National Science Open, 2022)
We recently demonstrated experimentally the synthesis of one-dimensional (1D) van der Waals (vdW) heterostructure, where single-crystal hexagonal boron nitride or molybdenum disulfide nanotubes seamlessly wrapped a single-walled carbon nanotube and formed a coaxial hetero-nanotube with the diameter typically being 1–5 nm. 1D vdW heterostructures have created large room for fundamental research from synthesis to application, but most directions are still at their initial stages. The materials that can be employed to construct 1D vdW heterostructures are limited to only a few types. In this review, we provide an outlook to the question: what are the building blocks available now and could be available in the future for the fabrication of 1D vdW heterostructures?